Le Massif du Sancy et Horizons – Arts Nature : quand Land Art rime avec attractivité - Marie-Ève Férérol (Revue de Géographie Alpine)
Since 2007, the Massif du Sancy (Puy de Dôme) has hosted the Horizons-Arts Nature festival. For the CRDT (Comité Régional de Développement Touristique/Regional Tourism Development Committee), this Land Art event "is a wonderful collision of art with nature". At first glance, the festival may indeed appear surprising for a region like Auvergne which is perceived as a less open-minded territory and an unlikely place for innovative activities.The object of this paper is twofold. First we want to understand the organisation and success of such an event in the region. What are the secrets to such a long run (10th edition in 2016)? Why are artists so inspired by the area? Is it the terrain that generates so much enthusiasm or simply the history of the site? We are also interested in the role culture plays in making the area attractive. In the Sancy mountain range, which of these reasons is behind Horizons - Arts Nature? What have local authorities and tourism professionals tried to achieve by creating the event?